Effect of turbulence and air velocity on radon progenys - Zelinskiy, A.S.; Yakovlev, G.A. (Vestnik KRAUNC: Fiziko-Matematičeskie Nauki, 2021)
In this paper, a simulation of the distribution of radon progeny over the height of the atmosphere, depending on the amount of turbulent mixing and the vertical air velocity, is presented. The obtained results are compared with the change in the activity ratio of Bi-214/Pb-214 isotopes recorded in rainwater during 3-year observations in Prague. It is found that the reasons for the most common values of Bi-214/Pb-214 can be the height of the lower edge of the cloud of 0.2-1.4 km and the vertical air velocity of 0.1 – 0.2 m / s. The ratio changes slightly from changes in the turbulent mixing, the value of the vertical air movement makes the main contribution. It is found that with the increase in the intensity of rain, a shift in the radioactive equilibrium should occur due to an increase in the velocity of vertical air. Atmospheric inversion is able to balance the volumetric activities of the descendants of atmospheric radon, atmospheric inversion can be identified by the equality between the activities of the radon progeny in the atmosphere at different altitudes or in rainwater. It is shown that the search for the relationship between precipitation intensity and gamma radiation is expose to error, without taking into account the influence of the АBi−214/АPb−214 ratio, due to the unequal activities of the atmospheric isotopes Bi-214 and Pb-214. This error of 7-14% when using gamma radiometry, and of 5-9% when using dosimeters is estimated.